Is Arabic Worth to Teach? - Naska, Isral (Modality Journal: International Journal of Linguistics and Literature, 2023)
AbstractThis research is a form of literature review that is part of my research that aims to investigate the views of Muslims in West Sumatra (Minangkabau Society) towards the Arabic language and how it drives their motivation to learn it. The lack of research on this issue in Indonesia, especially in the West Sumatran region, is the starting point of this study. In fact, a series of studies with the same theme have been conducted in various parts of the world such as in the United States (Belnap, 1987; Brosh, 2013; Husseinali, 2005, 2006; Nichols, 2014; Seymour-Jorn, 2004; Taha, 2007), Canada (Belnap, 1987), Malaysia (Abu et al., 2010; Aladin, 2010, 2013), Saudi Arabia (Al-Osaimi & Wedell, 2014), and the United Kingdom (Jaspal & Coyle, 2010). In terms of identity background, learners who establish some form of connection with the Arabic language are referred to as heritage learners (Brosh, 2013). I can conclude that religious identity is the strongest background that maintains Muslims' close relationship with Arabic.AbstrakPenelitian ini merupakan bentuk kajian pustaka yang merupakan bagian dari penelitian saya yang bertujuan untuk menyelidiki pandangan umat Islam di Sumatera Barat (Masyarakat Minangkabau) terhadap bahasa Arab dan bagaimana hal tersebut mendorong motivasi mereka untuk mempelajarinya. Minimnya penelitian tentang isu ini di Indonesia, khususnya di wilayah Sumatera Barat, menjadi titik tolak penelitian ini. Padahal, serangkaian penelitian dengan tema yang sama telah dilakukan di berbagai belahan dunia seperti di Amerika Serikat (Belnap, 1987; Brosh, 2013; Husseinali, 2005, 2006; Nichols, 2014; Seymour-Jorn, 2004; Taha, 2007), Kanada (Belnap, 1987), Malaysia (Abu dkk., 2010; Aladin, 2010, 2013), Arab Saudi (Al-Osaimi & Wedell, 2014), dan Inggris (Jaspal & Coyle, 2010). Dalam hal latar belakang identitas, pelajar yang menjalin hubungan dengan bahasa Arab disebut sebagai pelajar warisan (Brosh, 2013). Saya dapat menyimpulkan bahwa identitas agama merupakan latar belakang terkuat yang mempertahankan hubungan erat umat Islam dengan bahasa Arab.